Excessive Dynamic Airway Collapse: An Unexpected Contributor to Respiratory Failure in a Surgical Patient - Michael R. Lyaker; Victor R. Davila; Thomas J. Papadimos (Case Reports in Anesthesiology)
Central airway collapse plays a significant, underrecognized role in respiratory failure after extubation of critically ill patients. Historically, airway collapse has been attributed to tracheomalacia (TM), softening of the cartilage in the trachea and other large airways. More recently, excessive dynamic airway collapse (EDAC) has been described as a distinct process unrelated to a loss of cartilaginous airway support. EDAC is caused by the posterior wall of the trachea bulging forward and causing airway obstruction during exhalation. This process is exaggerated when intrathoracic pressure is increased and results in a clinical picture of coughing, difficulty clearing secretions, dyspnea, and stridor. The increased use of computerized tomography and fiberoptic bronchoscopy has identified varying degrees of EDAC and TM in both symptomatic and asymptomatic individuals. This has led to renewed consideration of airway collapse and the different processes that contribute to it. Here we describe a 43-year-old morbidly obese patient who failed repeated attempts at extubation after elective hysterectomy. We will discuss the processes of EDAC and TM, describe how this condition contributed to this patient’s respiratory failure, and review diagnosis and management options.